Neuromuscular, hormonal and oxidative stress responses to endurance running exercises in well-trained runners - Vuorimaa, T. (Studies in Sport, Physical Education and Health, 2007)
The aim of this study was to investigate to which type of running exercises well trained endurance runners respond more favourably with regard to acute neuromuscular and endocrinological responses and exercise-induced oxidative stress. It was hypothesized that these responses depend on the type of running exercise and relate to the physical characteristics. Altogether nine different running exercises and a long walking exercise were performed by a total of 88 male athletes. An intermittent exercise consisting of progressive 20 s runs decreased vertical jump performance in middle distance runners (MID), but improved it in marathon runners (MAR). An 18 - 24 min exhaustive test run, a 40 min intermittent run (IR) and a 40 min tempo run (TR), led to significant acute improvements in the vertical jump and half squat performance, simultaneously with a decrease in activation of the knee extensor muscles in well-trained endurance runners. The TR - induced improvement in half squat power correlated positively with the velocity associated with maximal oxygen uptake (VO2max) while the corresponding correlation in the case of IR was negative. IR resulted in a higher acute serum testosterone response and TR in a higher serum cortisol response in MID compared to MAR. The TR - induced increase in the molar ratio of serum testosterone to cortisol was the greater the higher the runners' VOzmax. Serum antioxidant capacity was shown to increase after three different endurance exercises of long duration in trained endurance athletes. An unexpected acute decrease in the moderately oxidized LDL was found after a low intensity 6h walking exercise but not after a 31-km intensive run or after a competitive marathon run. On the basis of the present results, it is likely that after intensive running the use of a different coordination strategy counteracts strength loss and even improves power in extension exercises performed vertically with both legs in well-trained endurance runners. It is also likely, that marathon runners respond more favourably to intensive continuous type of running with regard to acute leg extension power and hormonal changes while middle distance runners respond better to intermittent type of running. The present findings further suggest that, in well-trained endurance athletes, an acute exercise of long duration and low intensity may not increase oxidized LDL-cholesterol and thus not cause oxidative stress.